Pengaruh debt financing dan equity financing terhadap return on equity pada bank syariah yang terdaftar di bank indonesia - Teguh Yuli Indriyanto; Rusdiah Iskandar; Dwi Risma Deviyanti (AKUNTABEL, 2018)
This research was aimed to analyze the effect of Debt Financing and Equity Financing in Return on Equity Sharia Banking listed on Bank Indonesia. The dependent variable of research was Retun on Equity (ROE)  while the independent were Debt Financing and Equity Financing. The data used from the publication of annual reports of Sharia banks that publish their financial statements from 2015 to 2017. Data analysis technique used to answer the hypothesis is multiple linear regression analysis with spss tool 24 version. The result of the research shows that: (1) Debt Financing has significant effect to Return on Equity at BNI Syariah, Mega Syariah, Muamalat Indonesia Bank,         Mandiri Syariah from 2015 until 2017(2) Equity Financing has significant effect to Return on Equity on BNI Syariah, Mega Syariah, Muamalat Indonesia Bank, and Mandiri Syariah from 2015 to 2017.Key Words: Debt financing, Equity Financing, Return on Equity